Low‐frequency variability of precipitation in the North American monsoon region as diagnosed through earlywood and latewood tree‐ring chronologies in the southwestern US. (22nd September 2015) - Carrillo, Carlos M.; Castro, Christopher L.; Woodhouse, Connie A.; Griffin, Daniel
ABSTRACT: Recent studies have pointed out the statistical occurrence of dual‐season droughts detected in tree‐ring chronologies over the southwestern US region that is not well described by instrumental observed records of the 20th century. In this study, a multi‐statistical approach that evaluates persistent dual‐season drought using a mode‐of‐variability oriented approach is proposed, considering a new network of tree‐ring earlywood (EW)‐ and latewood‐adjusted (LWadj ) chronologies from throughout southwestern North America. To determine dominant patterns of spatiotemporal variability, empirical, orthogonal functions, canonical correlation analysis, and multi‐taper‐method singular value decomposition analyses were applied, with focus on variability from inter‐annual to centennial periods and highlighting the multi‐decadal signals inherent to proxy record network. During the instrumental period, we demonstrate that EW and LWadj networks of tree‐ring chronologies are able to capture the associated precipitation responses of cool and warm season atmospheric teleconnections. Considering the four‐century period of the complete tree‐ring network, we explore the possibility of a dual summer–winter variability signal in the low‐frequency climate regime. EW and LWadj seem to be coherent in‐phase at the very low‐frequency scale (50–100 years spectral band). This provocative result is supported by major historic documented multi‐year droughts of the region since 1650. Thus, the temporal variation of these chronologies time series and its associated spatial pattern strongly suggest that this low‐frequency mode might represents an important spatiotemporal variation of droughts in the Southwest; however, the source of this signal is still an open question and of great interest for drought planning and resource management in the region.